Patient-Reported Outcomes for Migraine in the US and Europe: Burden Associated with Multiple Preventive Treatment Failures - Ford J; Nichols RM; Ye W; Tockhorn-Heidenreich A; Cotton S; Jackson J (Dove Medical Press, 2021)
Janet Ford,1 Russell M Nichols,1 Wenyu Ye,1 Antje Tockhorn-Heidenreich,1 Sarah Cotton,2 James Jackson2 1Eli Lilly and Company, Indianapolis, IN, USA; 2Adelphi Real World, Bollington, UKCorrespondence: Janet FordEli Lilly and Company, Indianapolis, IN, 46285, USATel +1 317-903-8199Email ford_janet@lilly.comPurpose: To evaluate patient-reported outcomes (PROs) among patients with migraine, including those who were preventive-naïve and preventive-treated.Methods: This was a point-in-time, real-world study of patients with migraine in the US and EU5 (France, Germany, Spain, Italy, and UK) and their physicians using data from the Adelphi Migraine Disease Specific Programme (DSP™). Physicians completed patient record forms (PRFs) for the next nine consulting patients with migraine plus a tenth patient, who did not need to be consecutive, for whom prior preventive migraine treatments had failed at least once, in order to achieve oversampling of such patients. Patients were given self-completion (PSC) forms that included the Migraine-Specific Quality of Life Questionnaire v2.1 (MSQ), Migraine Disability Assessment Scale (MIDAS), and Work Productivity and Activity Impairment (WPAI) questionnaire. Populations of interest included preventive-naïve and preventive-treated patients defined by the number of treatment lines (1- 2 or 3+ preventive regimens). Continuous variables were compared using t-test or ANOVA if normally distributed and Mann-Whitney if not. Chi-squared was used for categorical variables.Results: During August-December 2017, 615 physicians (359 PCPs, 256 neurologists) completed PRFs for 5785 patients (71% female; mean age 40 (± 14) years; 65% in full- or part-time employment). Of these, 2798 completed a PSC (preventive-naïve/1- 2/3+ preventive lines, n=1707/1034/57). Preventive-treated patients had a greater patient-reported burden across multiple measures versus preventive-naïve patients. Preventive-treated patients had lower MSQ scores indicating greater functional impairment, higher MIDAS scores indicating greater migraine-associated disability, and higher WPAI scores indicating greater overall work and activity impairment than preventive-naïve patients. The magnitude of difference was greatest for the 3+ preventive-treatments cohort. Patterns were similar in the US and EU5.Conclusion: Among patients with migraine who are preventive-treated, including those with multiple lines of therapy, there remain considerable unmet needs in terms of restoring patient function.Keywords: migraine, preventive, patient-reported outcomes, real-world